EPIDEMIOLOGICAL ANALYSIS OF CHILD SEXUAL VIOLENCE: A DESCRIPTIVE RESEARCH - Sousa Oliveira, Juliana; de Oliveira Dias, Gerson; José Pinheiro Araújo, Francisco; Morais Silva, Gabriel; Eduarda Araujo Florêncio, Maria; Pereira dos Santos Junior, Adeildo; Vinícius Pereira de Oliveira, Arthur; Eduarda Abreu de Oliveira, Maria; Furtado Lucena Dos Santos, Aryanny; Molinare de Araújo Maciel, Dalila; Alves de Sousa, Karen; Álamo Furtado Lucena, Francisco; et al. (Health and Society, 2025)
Child sexual violence is a serious public health problem in Brazil, with devastating impacts on the physical, psychological, and social development of victims. The epidemiological analysis carried out, based on data from DATASUS between 2015 and 2021, revealed a high incidence of cases of child sexual violence in the country, with a predominance of female victims and male aggressors. São Paulo, Minas Gerais, and Rio de Janeiro had the highest numbers of confirmed cases, reflecting both greater exposure and effectiveness in reporting these incidents. On the other hand, states with less health infrastructure, such as Roraima and Amapá, showed significantly lower numbers, suggesting difficulties in detection and reporting. The research also identified the large number of unconfirmed cases and blank data, which indicates flaws in the process of collecting and recording information. The relationship between victims and aggressors is predominantly familial, highlighting the importance of prevention strategies aimed at strengthening the protection network and raising awareness among the population, especially in schools and in the family environment. Despite advances in public policies, such as the Health in Schools Program, the implementation of preventive and educational actions still faces challenges, including cultural resistance and lack of resources, which highlights the need for a more integrated and effective approach between health, education and social assistance. Thus, the research highlights the importance of strengthening existing public policies and improving detection, reporting and support for victims of child sexual violence in Brazil.